Karakteristik Campuran AC-BC Menggunakan Batu Gunung Sebagai Agregat Kasar dan Abu Vulkanik Sebagai Filler - Rahmi, Novita; Hermanto, Edy; Lubis, Kamaluddin (Jurnal Ilmiah Teknik Sipil dan Arsitektur (JITAS), 2025)
Pavement is a system consisting of several layers of material that is placed on the subgrade. The main purpose of pavement construction is to provide a flat surface with a certain toughness, with a sufficiently long service life, and minimum maintenance. The population growth in Indonesia is very fast, which can result in an increase in population mobility in Indonesia. So that many heavy vehicles appeared on the highway. Therefore, the government continues to spur infrastructure development in Indonesia. One of the basic ingredients for road infrastructure development is filler. Pavement above ground is usually formed from several layers that are relatively weak at the bottom, and gradually stronger at the top. With this research, it is hoped that it can provide understanding and add insight into the effect of using mountain rock as coarse aggregate and volcanic ash as a filler in hot asphalt mixture, especially AC-BC as a flexible pavement binder layer in terms of marshall properties (stability, flow, void in mineral aggregate (VMA), void in the mix (VIM), void filled with asphalt (VFA) and Marshall Quotient). From the data from the Marshall test test results for the AC BC asphalt mixture with different bitumen variations, the optimum asphalt content was 5.57%.  Meanwhile, from the different aggregate variations using the optimum bitumen content, the asphalt mixture using natural stone aggregates has a stability value of 1190.8 kg, so it can be used in the planning of a local pavement with low traffic volume.